Referential Range Of The Pulsatility Index Of The Uterine Artery In Fetus Healthy Maternal Perinatal National Institute 2010 To 2016 - Limay-Ríos, Oscar Antonio (2017)
Objectives: Set the values for reference index pulsatilidad of artery uterine between 11-41 weeks of gestation in fetuses healthyin the maternal perinatal national institute in the period 2010 to 2016. Desing: Retrospective Cross-sectional descriptive study.Participants: Healthy fetuses. Main outcome measures: Reference ranges of the uterine artery pulsatility index.